ANTESEDEN NIAT UNTUK MEMLIH JASA HALAL BEAUTY CENTER: APLIKASI THEORY OF PLANNED BEHAVIOR DAN PERAN RELIGIUSITAS - Chandra Suparno (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2017)
Â AbstractThis research aims to analyze the influence of attitude, subjective norm, and perceived behavior control towards intention to choose halal beauty center with the Islamic religiousity as the moderating variable. This study took 120 respondents as its samples by using accidental and purposive sampling as the method to collect the sample. Using Multiple Regression Analyis, and Chow test, the results of this study shows that attitude and subjective norm have a positive influence towards intention to choose muslimah beauty center. It also revealed that religiousity moderates the relation between attitude, subjective norm and intention to choose halal beauty center.Â This research aims to analyze the influence of attitude, subjective norm, and perceived behavior control towards intention to choose halal beauty center with the Islamic religiousity as the moderating variable. This study took 120 respondents as its samples by using accidental and purposive sampling as the method to collect the sample. Using Multiple Regression Analyis, and Chow test, the results of this study shows that attitude and subjective norm have a positive influence towards intention to choose muslimah beauty center. It also revealed that religiousity moderates the relation between attitude, subjective norm and intention to choose halal beauty center.